Comparison of Economic Growth, Agricultural Sector, and Household Consumption Before and After The Free Nutritious Meal Program (MBG) in Districts With The Highest And Lowest Hdi in South Sumatra - Megry Fatra Humbara; Abdul Basyith; Delvina Yulanda (Journal of Management, Economic, and Accounting, 2026)
The Free Nutritious Meal Program (MBG) is a national priority policy of the Indonesian Government for the 2024–2029 period aimed at improving children's nutrition while simultaneously stimulating the local economy. This study analyzes the comparative impact of MBG on economic growth, the agricultural sector, and household consumption before and after program implementation in South Sumatra, as well as comparing its effectiveness between high and low Human Development Index (HDI) regions. The research employed a comparative quantitative approach with a before-after design across 17 districts/cities, focusing on three highest HDI regions (Palembang City, Prabumulih, Lubuklinggau) and three lowest HDI regions (Empat Lawang, South OKU, PALI). Data were analyzed using descriptive statistics, paired sample t-tests, and simple linear regression with SPSS version 25. The results indicate that MBG has a significant positive effect on economic growth (β=0.348; p<0.001) and the agricultural sector (β=1.945; p<0.001), but a negative impact on household consumption (β=-0.514; p<0.001). The economic impact was greater in low HDI areas, with an economic growth increase of 0.40 percentage points compared to only 0.14 percentage points in high HDI areas. These findings support prioritizing MBG implementation in disadvantaged regions for more inclusive development.